2010
DOI: 10.1007/s12665-010-0785-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variations of δ2H and δ18O in precipitation and shallow groundwater in the Hilly Loess Region of the Loess Plateau, China

Abstract: Groundwater is of utmost significance to socioeconomic development and ecological recovery for the Loess Plateau. However, studies regarding the mechanism governing groundwater recharge over this area appear to be inadequate. This study is to examine the spatio-temporal variations of d 2 H and d 18 O in precipitation and shallow groundwater. On the basis of this, the mechanisms governing shallow groundwater recharge were explored. Precipitation and groundwater were sampled monthly from May to October during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…It is difficult to find the traditional ‘isotopic altitude and latitude effect’ for precipitation (Yang et al ., ) and in groundwater. According to the only basin‐scale study in the LPC, an ‘altitude effect’ for precipitation does not occur during the summer monsoon (Liu et al ., ). This suggests that in the semiarid LPC, groundwater is recharged by seasonal large rainfall with rapid infiltration and not much evaporation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It is difficult to find the traditional ‘isotopic altitude and latitude effect’ for precipitation (Yang et al ., ) and in groundwater. According to the only basin‐scale study in the LPC, an ‘altitude effect’ for precipitation does not occur during the summer monsoon (Liu et al ., ). This suggests that in the semiarid LPC, groundwater is recharged by seasonal large rainfall with rapid infiltration and not much evaporation.…”
Section: Resultsmentioning
confidence: 97%
“…Stable isotopic compositions for shallow groundwaters from the study area (elevation = 1800–1900 m, a.s.l. ), the Ansai terrace (1100–1200 m; Gates et al ., ), the Chibagou hilly region (898–1302 m); (Liu et al ., ) and typical loess plains, e.g. Changwu (~1200 m; Wang, ), Xifeng (~1420 m), Luochuan (~1150 m; Huang, ) and Xi'an (400–1200 m; Qin and Tao, ) are all close to the GMWL and are depleted in heavy isotopes (Figure ), compared with the weighted average of −6.6‰ for precipitation from Yinchuan (1112 m) in the northern LPC, −7.1‰ from Xi'an (400 m) in the south (IAEA and WMO, ) and −7.8‰ in the Ordos Basin (Yang et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al . () concluded that the spatio‐temporal variations of precipitation isotopic compositions in the Loess Plateau are dominated by the difference in water vapour origin, monsoon intensity and hydrological processes. As indicated from the diagrams of monthly variation of δ 2 H and δ 18 O (Figure a and c), the isotopes of precipitation in high mountain–hills of the Loess Plateau also show regular seasonal variations.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies documenting tracer movement in the soil column have pointed to the existence of preferential fluid flow through vertical fissures, macropores, cracks, decayed plant roots and earthworm burrows to rapidly recharge groundwater (Roy and David, ; Yan and Wang, ; Van Ommen et al ., ; Komor and Emerson, ; Ritsema et al ., ; Gehrels et al ., ; Ritsema and Dekker, ; Vincent et al ., ; Gates et al ., ; Yasuda et al ., ). Rainfall infiltration has also been assumed to be more like a piston infiltration mode to slowly percolate downward and recharge groundwater (Yan, ; Qu, ; Zhang et al ., ; Lin and Wei, ; Huang et al ., ) or two modes of piston and preferential flow may simultaneously exist to recharge groundwater (Gazis and Feng, ; Xu et al ., ; Liu et al ., , ). Some studies conclude that the depleted isotopic signature of loess groundwater may be also consistent with isotopic compositions of palaeo‐waters in northern China, where the groundwater may have been recharged during glacial–interglacial transitional periods (Chen et al ., ; Currell et al ., ; Gates et al ., ; Liu et al ., ).…”
Section: Introductionmentioning
confidence: 98%